2003
DOI: 10.1103/physrevb.68.205401
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational states of a H monolayer on the Pt(111) surface

Abstract: We present high-resolution electron energy-loss data and theoretical modeling for the vibrational properties of an atomic monolayer of H ͑D͒ on the Pt͑111͒ surface. Experimentally we find three loss peaks, in contrast with two peaks visible in the low-coverage case. A three-dimensional adiabatic potential-energy surface at full coverage of hydrogen is obtained through first-principles calculations. When the zero-point energy effects are included, the minimum energy adsorption site is found to be the fcc site j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…These theoretical results are consistent with previous experimental results [2,3,9,11,13,16,19] which indicated that only one type of H a (H a on fcc sites) exists on the Pt(111) surface. The adsorption energy of H a on the fcc sites of Pt(111) decreases by 0.14 eV/atom when the surface coverage is increased from 0.25 ML to 1.0 ML, which clearly shows that strong repulsive interactions exist within H a layers on Pt(111) at high coverages.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These theoretical results are consistent with previous experimental results [2,3,9,11,13,16,19] which indicated that only one type of H a (H a on fcc sites) exists on the Pt(111) surface. The adsorption energy of H a on the fcc sites of Pt(111) decreases by 0.14 eV/atom when the surface coverage is increased from 0.25 ML to 1.0 ML, which clearly shows that strong repulsive interactions exist within H a layers on Pt(111) at high coverages.…”
Section: Resultssupporting
confidence: 92%
“…Two similar desorption peaks have been also observed in previous investigations [2,17,22], and attributed to repulsive H···H interactions between the dissociatively adsorbed H atoms on Pt(111) at 110 K. The slight differences in desorption temperature and relative peak intensity between our results and those in the literature may be due to different adsorption temperatures and heating rates. Considering that the adsorption temperature is around 110 K in our TDS measurements, we assume [2] that the saturation coverage of H a on Pt(111) is 1 ML. The desorption activation energy of the  2 peak was determined by employing the leading edge analysis method [17].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations